Assessing Translation Accuracy of Informative Texts in Berita2Bahasa.com - Syafa Audrina; Moh Supardi; Hilmi Akmal; Sholikatus Sa'diyah (Journal of Translation, Linguistics and Literature, 2026)
This study analyzed the accuracy of informative text translation on the bilingual website Berita2Bahasa.com. Using a descriptive mix  method, the research applied Larson's (1998) translation theory and Nababan's (2012) accuracy assessment model. The dataset comprised 20 data points from four political news articles. Findings indicated an average accuracy score of 2.5 on a 3-point scale, with 60% accurate, 20% less accurate, and 3.33% inaccurate translations. The article Indonesians Vote in Regional Election Seen as Test for Prabowo  was the most accurate. This study concluded the importance of maintaining original meaning and cultural context in political news translations.